Pré-Enem Digit@l MT: Potencialização do Ensino para Recomposição da Aprendizagem - Sousa, Edna Maria Carvalho de; Lanzoni, Valéria Aparecida; Silva, Lilia de Oliveira; Souza, Vanessa Ferreira de (Anais Estendidos do Seminário de Educação (SemiEdu), 2024)
Este artigo não possui um resumo.